2020
DOI: 10.3389/fneur.2020.00155
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effect of Combined Mirror Therapy on Upper Extremity in Patients With Stroke: A Systematic Review and Meta-Analysis

Abstract: Background: There is an increasing trend for researchers to combine mirror therapy with another rehabilitation therapy when treating the upper extremity of patients with stroke.Objective: To evaluate the synergistic effect of combined mirror therapy (MT) on the upper extremity in patients with stroke and to judge efficacies of four combined mirror therapy subgroups [EMGBF group: electromyographic biofeedback (EMGBF) + MT; MG group: mesh glove (MG) + MT; AT group: acupuncture (AT) + MT; ES group: EMG-triggered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 40 publications
2
23
1
Order By: Relevance
“…Due to the lack of systematic review or meta-analysis analyzing the synergic effect of this intervention, the present findings will be compared to similar, though not specific, research. Contrary to our findings, Luo et al 28 concluded that mirror therapy combined with other treatment modalities was effective to improve upper extremity motor function in stroke patients compared with conventional therapy. However, the authors were not specifically focused on analyze the effects of the simultaneous combination of mirror therapy and electrical stimulation, and the heterogeneity of the studies included in the meta-analysis was high.…”
Section: Discussioncontrasting
confidence: 99%
“…Due to the lack of systematic review or meta-analysis analyzing the synergic effect of this intervention, the present findings will be compared to similar, though not specific, research. Contrary to our findings, Luo et al 28 concluded that mirror therapy combined with other treatment modalities was effective to improve upper extremity motor function in stroke patients compared with conventional therapy. However, the authors were not specifically focused on analyze the effects of the simultaneous combination of mirror therapy and electrical stimulation, and the heterogeneity of the studies included in the meta-analysis was high.…”
Section: Discussioncontrasting
confidence: 99%
“…However, due to the small sample size and large heterogeneity of patients (including the locations and side of brain injury, motor and cognitive impairment levels, sensory function, and even age, etc.) (Luo et al, 2020), the clinical efficacy and related mechanisms of MVF still needs further analysis. More recently, the Central-Peripheral-Central closed-loop regulation mode, formed by the combination of MVF as a central intervention method with other peripheral interventions, has become a research hotspot to further improve the technique.…”
Section: Introductionmentioning
confidence: 99%
“…The results of this analysis suggest that the effects on both motor function and impairment of the affected upper limb depend on the therapy protocol [51]. Combining mirror therapy with another rehabilitation therapy on the upper extremity in patients with stroke is better than single rehabilitation therapy [52]. Among them, Additional mirror therapy in combination with EMG-This document was downloaded for personal use only.…”
Section: Discussionmentioning
confidence: 98%